Pengaruh Penggunaan Mikroorganisme Lokal (MOL) Cairan Rumen Sapi Pada Level Inokulum yang Berbeda terhadap Nilai Kandungan Serat Jerami Padi Terfermentasi - Lodovitus Aman; Stefanus Sio; Gerson Frans Bira (JAS, 2022)
Feed is one of the most important factors for livestock productivity. One of the obstacles in the development of the livestock business is the lack of availability of feed ingredients in terms of quantity, quality, and continuity. The need for feed is not constant because forage is very dependent on the season, where in the rainy season, feed is very abundant, and in summer, the availability of feed is very less. One way to overcome this is to use rice straw as an alternative feed for livestock, which is abundantly available during the harvest season. However, rice straw has high ADF, NDF, lignin and cellulose content, so rice straw needs to be processed. This study aims to determine the effect of using local microorganisms (MOL) of cow rumen fluid at different inoculum levels on the quality of fermented rice straw to overcome the lack of feed in certain seasons. The study used a completely randomized design (CRD) with 4 treatments and 4 replications, namely R0: 87% rice straw + 10% rice bran + 3% molasses (without MOL of cow rumen fluid/control); R1: Rice Straw 87% + Rice Bran 10% + molasses 3% + MOL cow rumen fluid 5%; R2: Rice Straw 87% + Rice Bran 10% + molasses 3% + MOL cow rumen fluid 10%; R3: Rice Straw 87% + Rice Bran 10% + molasses 3% + MOL beef rumen fluid 15%. The percentage of molasses and cow's rumen fluid was adjusted to the weight of chopped rice straw and the data were analyzed using analysis of variance (Anova). The results showed that the treatment had a significant effect (P<0,05) on the ADF, NDF, lignin, and cellulose content of rice straw. It can be concluded that the higher the level of MOL use of cow rumen fluid, the lower the content of ADF, NDF, lignin, and cellulose in rice straw.